Examining attributes affecting fast-food restaurants’ self-service ordering kiosk continuous usage intention - Hashim, Muhammad Hanif; Ngelambong, Anderson; Abdullah, Dahlan; Kom, Campiranon (Universiti Teknologi Mara Cawangan Pulau Pinang, 2023)
Self-service ordering kiosks are gaining popularity among fastfood operators to reduce operational costs. Although there is an abundance of study on the subject, limited studies have investigated the antecedents of self-service ordering continuous usage intention from the perspective of the information system success model. Understanding what continuously influences customers to use selfservice ordering kiosks is essential to justifying the enormous technological investments. Thus, the study investigates attributes influencing customers' continuous usage of automated self-service technology in fast-food restaurants, explicitly focusing on Penang, Malaysia. Unlike the existing studies, the study employed Delone and Mclean’s information success model as the underpinning theory that can contribute to a new perspective in the current literature. The statistical analyses found that system quality, innovativeness, safety, and security significantly influence continuous usage intention. The study’s findings suggest that fastfood restaurant operators should focus on enhancing the quality, safety, and security of their self-service ordering kiosks. The study also highlighted the importance of innovativeness as an attribute of customers’ intention to use self-service ordering kiosks. Customers are more likely to continuously operate a self-service ordering kiosk if they think it is more advanced than traditional ordering methods. Several study limitations were discussed, which serve as signposts for future research endeavors.